Dissecting Torsin/cofactor function at the nuclear envelope: a genetic study - Laudermilch, Ethan; Tsai, Pei-Ling; Graham, Morven; Turner, Elizabeth; Zhao, Chenguang; Schlieker, Christian (Molecular biology of the cell, 2016)
The human genome encodes four Torsin ATPases, the functions of which are poorly understood. In this study, we use CRISPR/Cas9 engineering to delete all four Torsin ATPases individually and in combination. Using nuclear envelope (NE) blebbing as a phenotypic measure, we establish a direct correlation between the number of inactivated Torsin alleles and the occurrence of omega-shaped herniations within the lumen of the NE. A similar, although not identical, redundancy is observed for LAP1 and LULL1, which serve as regulatory cofactors for a subset of Torsin ATPases. Unexpectedly, deletion of Tor2A in a TorA/B/3A-deficient background results in a stark increase of bleb formation, even though Tor2A does not respond to LAP1/LULL1 stimulation. The robustness of the observed phenotype in Torsin-deficient cells enables a structural analysis via electron microscopy tomography and a compositional analysis via immunogold labeling. Ubiquitin and nucleoporins were identified as distinctively localizing components of the omega-shaped bleb structure. These findings suggest a functional link between the Torsin/cofactor system and NE/nuclear pore complex biogenesis or homeostasis and establish a Torsin-deficient cell line as a valuable experimental platform with which to decipher Torsin function.